The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1021/acs.jmedchem.7b00717
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Rule of 5: Lessons Learned from AbbVie’s Drugs and Compound Collection

Abstract: Recently, there has been an increasing focus on the pursuit of targets considered to be less druggable that offer potential for development of promising new therapeutic agents for the treatment of diseases with large unmet medical need, particularly in the areas of oncology and virology. However, conducting drug discovery campaigns in "beyond rule of 5" (bRo5) chemical space presents a significant drug design and development challenge to medicinal chemists to achieve acceptable oral pharmacokinetics. Retrospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
288
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 294 publications
(325 citation statements)
references
References 64 publications
7
288
0
3
Order By: Relevance
“…First, the drug/lead-likeness criteria forp hysicochemical properties (first, the Ro5) are challenged by compounds from beyondt he rule of five (bRo5)c hemical space (e.g.,a ntiviral agents Simeprevir and Ledipasvir). [252] Next, the relevance of substructural filters is confronted by covalent ligands bearing classicale lectrophilic moieties, such as Michael acceptors (e.g., anticancer agent Afatinib). [253] Both types of these "rule breakers" are discussed in sections 4.1 and 4.2.…”
Section: Toom Any Rules For Drug Discovery?mentioning
confidence: 99%
“…First, the drug/lead-likeness criteria forp hysicochemical properties (first, the Ro5) are challenged by compounds from beyondt he rule of five (bRo5)c hemical space (e.g.,a ntiviral agents Simeprevir and Ledipasvir). [252] Next, the relevance of substructural filters is confronted by covalent ligands bearing classicale lectrophilic moieties, such as Michael acceptors (e.g., anticancer agent Afatinib). [253] Both types of these "rule breakers" are discussed in sections 4.1 and 4.2.…”
Section: Toom Any Rules For Drug Discovery?mentioning
confidence: 99%
“…To bridge the gap between small molecules and biologics, compounds in the beyond rule of 5 (bRo5) space, such as peptides, peptidomimetics and macrocycles, are currently attracting major interest . By analysis of a comprehensive set of >200 orally administered drugs and clinical candidates residing in bRo5 space we have shown that bRo5‐ligands provide improved opportunities for the modulation of difficult‐to‐drug targets .…”
Section: Introductionmentioning
confidence: 99%
“…The emerging interest for IMHBs can be summarized as follows: IMHB formation can mask polar groups and thus impact upon the triad of permeability, solubility, and potency of drugs and candidates. IMHB modulation is, therefore, a promising strategy that can be applied to any chemical space (small molecules and beyond rule of 5 [bRo5]) as a means of discovering drug candidates with both acceptable potency and ADME‐Tox profiles …”
Section: Introductionmentioning
confidence: 99%
“…IMHB modulation is, therefore, a promising strategy that can be applied to any chemical space (small molecules and beyond rule of 5 [bRo5]) as a means of discovering drug candidates with both acceptable potency and ADME-Tox profiles. [5][6][7][8][9][10] Currently, peptides are probably the most appreciated bRo5 derivatives by pharmaceutical researchers. They are easily accessible via solid phase synthesis, highly selective, relatively safe, and well tolerated.…”
Section: Introductionmentioning
confidence: 99%